Visualization and characterization of pre-breakdown processes in the volume of a ZnGeP2 single crystal during parametric generation of radiation in the wavelength range of 3.5–5 μm when pumped by Ho: YAG laser radiation - Yudin, Nikolay N.; Vlasov, Denis V.; Antipov, Oleg L.; Gribenyukov, Alexander I.; Zinoviev, Mikhail M.; Podzyvalov, Sergey N.; Slyunko, Elena S.; Yudin, Nikolay A.; Kulesh, Maksim M.; Kuznetsov, Vladimir S.; Dyomin, Victor V. (Russian physics journal)
The energy characteristics and the results of visualization of processes occurring in the volume of a crystal recorded with a digital holographic camera have been studied. It is established that the parametric generation efficiency ceases to increase when the pump energy density exceeds 1 J/cm2 , and darkening of the laser radiation propagation channel in the crystal volume is observed. It is also shown that the transmission of laser radiation decreases when the energy densities exceed 1 J/cm2.